High sensitivity troponins discriminate different morphologies of coronary artery plaques being assessed by coronary computed tomography angiography - Rusnak, Jonas; Behnes, Michael; Reckord, Nadine; Hoffmann, Ursula; Natale, Michèle; Hoffmann, Julia; Weidner, Kathrin; Lang, Siegfried; Mukherji, Agnibh; Kruska, Mathieu; Henzler, Thomas; Schönberg, Stefan; et al. (Disease markers, 2017)
Background. This study evaluates the association between high sensitivity troponin I (hsTnI) and T (hsTnT) and the morphology of coronary artery plaques detected by coronary computed tomography angiography (CCTA) in patients with suspected coronary artery disease (CAD). Methods. Patients undergoing CCTA were prospectively enrolled. CCTA was indicated by a low to intermediate pretest probability for CAD during routine clinical care. Within 24 hours of CCTA examination, peripheral blood samples were taken to measure hsTnI, hsTnT, and N-terminal probrain natriuretic peptide (NT-proBNP). Results. A total of 99 patients were enrolled with 43% without CAD, 9% with noncalcified plaques, 28% with calcified plaques, and 19% with mixed type plaque lesions. Both hsTnI and hsTnT levels were able to discriminate significantly between the groups, especially in the presence of mixed coronary plaques (AUC range: 0.741-0.752; ). In multivariate logistic regression models, hsTnT, but not hsTnI, was still significantly associated with mixed coronary plaque morphology (odds ratio = 8.968; 95% CI 1.999-40.241; ). Conclusions. Both hsTnI and hsTnT are able to discriminate between different coronary artery plaques morphologies, whereas hsTnT was significantly associated with mixed coronary plaques in patients with suspected CAD. This trial is registered with NCT03074253.
Gesehen am 26.04.2018